Cytosolic Guanine Nucledotide Binding Deficient Form of Transglutaminase 2 (R580a) Potentiates Cell Death in Oxygen Glucose Deprivation - Colak, Gozde (Public Library of Science, 2011)
Transglutaminase 2 (TG2) is a hypoxia-responsive protein that is a calcium-activated transamidating enzyme, a GTPase and a scaffolding/linker protein. Upon activation TG2 undergoes a large conformational change, which likely affects not only its enzymatic activities but its non-catalytic functions as well. The focus of this study was on the role of transamidating activity, conformation and localization of TG2 in ischemic cell death. Cells expressing a GTP binding deficient form of TG2 (TG2-R580A) with high basal transamidation activity and a more extended conformation showed significantly increased cell death in response to oxygen-glucose deprivation; however, targeting TG2-R580A to the nucleus abrogated its detrimental role in oxygen-glucose deprivation. Treatment of cells expressing wild type TG2, TG2-C277S (a transamidating inactive mutant) and TG2-R580A with Cp4d, a reversible TG2 inhibitor, did not affect cell death in response to oxygen-glucose deprivation. These findings indicate that the pro-cell death effects of TG2 are dependent on its localization to the cytosol and independent of its transamidation activity. Further, the conformational state of TG2 is likely an important determinant in cell survival and the prominent function of TG2 in ischemic cell death is as a scaffold to modulate cellular processes.